2006
DOI: 10.1186/1471-2334-6-93
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the force of infection for hepatitis B and hepatitis C in injecting drug users in England and Wales

Abstract: Background: Injecting drug use is a key risk factor, for several infections of public health importance, especially hepatitis B (HBV) and hepatitis C (HCV). In England and Wales, where less than 1% of the population are likely to be injecting drug users (IDUs), approximately 38% of laboratory reports of HBV, and 95% of HCV reports are attributed to injecting drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 14 publications
5
77
0
Order By: Relevance
“…20,92 There are four injecting duration categories: < 3 years, ≥ 3 years to < 10 years, ≥ 10 years and ex-injecting drug users. All PWID enter the model as recently initiated PWID (< 3 years injecting category) at a constant rate θ, and then transition to non-recent PWID (at rate 1/3 year -1 ) and then to long-term PWID (at a rate of 1/7 year -1 from the non-recent PWID).…”
Section: Model Descriptionmentioning
confidence: 99%
“…20,92 There are four injecting duration categories: < 3 years, ≥ 3 years to < 10 years, ≥ 10 years and ex-injecting drug users. All PWID enter the model as recently initiated PWID (< 3 years injecting category) at a constant rate θ, and then transition to non-recent PWID (at rate 1/3 year -1 ) and then to long-term PWID (at a rate of 1/7 year -1 from the non-recent PWID).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The incidence of HBV infection among susceptible PWID in the United Kingdom was estimated at 2.16% per year using data from the national Unlinked Anonymous Monitoring Survey among current and past injectors and an approach similar to Sutton et al 23. Additional details are provided in the Supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that younger IDUs with shorter injecting career lengths are at increased risk of blood-borne virus infection compared to more experienced IDUs [14]. Therefore it is of interest to consider whether a pulse or continuous vaccination strategy would be better at capturing younger IDUs for vaccination.…”
Section: Discussionmentioning
confidence: 99%